2019
DOI: 10.1111/1462-2920.14751
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonization of minerals in grassland soils is selective and highly dynamic

Abstract: Summary Bacteria colonize reactive minerals in soils where they contribute to mineral weathering and transformation. So far, the specificity, patterns and dynamics of mineral colonization have rarely been assessed under natural conditions. High throughput Illumina sequencing was employed to investigate the bacterial communities assembling on illite and goethite during exposure to natural grassland soils. Two different types of organic carbon sources, simple carbon compounds representing root exudates and detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 87 publications
(139 reference statements)
3
26
0
Order By: Relevance
“…In this context, the co‐occurrence network for the soil microbiota was more stable in alpine grassland soils with a neutral pH than in acidic or alkaline soils. Numerous researches have suggested that ‘acidity specialists’ habitat in acidic soils and ‘alkalinity specialists’ in alkaline soils (Jones and Bennett, 2017; Vieira et al ., 2020). Among the low‐pH cluster microbial taxa that we detected, Bradyrhizobium species had been shown to favour low‐pH environments (Bottomley et al ., 1991; Graham et al ., 1994); and Nitrososphaera species from the high‐pH cluster, favours high‐pH environments (Zhalnina et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the co‐occurrence network for the soil microbiota was more stable in alpine grassland soils with a neutral pH than in acidic or alkaline soils. Numerous researches have suggested that ‘acidity specialists’ habitat in acidic soils and ‘alkalinity specialists’ in alkaline soils (Jones and Bennett, 2017; Vieira et al ., 2020). Among the low‐pH cluster microbial taxa that we detected, Bradyrhizobium species had been shown to favour low‐pH environments (Bottomley et al ., 1991; Graham et al ., 1994); and Nitrososphaera species from the high‐pH cluster, favours high‐pH environments (Zhalnina et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The most labile C components in rhizodeposition are root exudates (Grayston et al 1997), which consist predominantly of sugars, amino acids, and organic acids (van Hees et al 2005). They are known to increase soil microbial activity and abundance and to affect microbial community composition (Grayston et al 1997;Rovira 1969;Strickland et al 2015;Vieira et al 2020). Glucose, glycine, and oxalic and citric acids have frequently been used to study the microbial response after addition of artificial root exudates (Eilers et al 2010;Strickland et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our approach exposed organo-mineral complexes, represented by pristine minerals loaded with ARE, in mineral containers in the topsoil of ten grassland sites of different land-use intensities of the Biodiversity Exploratories at the Schwäbische Alb (south-west Germany). Whereas Vieira et al (2020) used the same experimental set-up as the present study to describe bacterial community succession during one season, we present high-resolution temporal data on both the succession of organic compounds associated with minerals and of bacterial and fungal C use dynamics over one growth season. Specifically, we hypothesized that (1) the mineral-associated organic matter will be modified by colonizing microorganisms and/or by the input of soil-derived DOC;…”
Section: Introductionmentioning
confidence: 99%
“…For determination of total bacterial counts, an aliquot of each sample was fixed in 1% glutardialdehyde and stored at 4°C until analysis. Samples were stained with SYBR Green and filtered onto black 0.2 µm isopore membrane filters (Merck Millipore, Darmstadt, Germany) (Vieira et al ., 2019). Filters were placed between object slide and coverslip and sealed with nail polish, and images were monitored employing a Nikon Eclipse Ti inverted microscope with GFP (485/20‐525/30) filters.…”
Section: Methodsmentioning
confidence: 99%